Formulasi Sediaan Pemerah Pipi Ekstrak Air Buah Syzygium cumini dalam Bentuk Compact Powder - Letelay, Yulia Riani; Darsono, Farida Lanawati; Wijaya, Sumi (Jurnal Farmasi Sains dan Terapan, 2017)
One of the fruits in Indonesia that can be used in the field of decorative cosmetics is Syzygium cumini. Blackish purple appearance of the fruit indicates the high content of anthocyanin, a natural pigment dye in decorative cosmetic formulations, especially for blusher. Compact powder blusher has the advantage of easy to use and has a better adhesion to the skin. Isopropyl myristate is a binder that is commonly used for compact powder blusher because of its properties which can increase adhesivity. The purpose of this study was to determine the effect of the concentration of isopropyl myristate as a binder on physical quality and effectiveness and to determine the best formula that fulfil the requirement of the physical quality, effectiveness, safety and acceptability. The compact powder blusher containing water extract of Syzygum cumini was formulated using wet granulation method with varying concentrations of isopropyl myristate 0.5%, 0.75% and 1.0%. The Evaluation of the product includes organoleptic, homogeneity, particle size, pH, friability and hardness, rubbing test, irritation test and acceptability test. The results showed an increase in the concentration of isopropyl myristate had a significant effect on decreasing the pH value, decreasing particle size, and affecting the ability of the blusher to be smeared. The compact powder blusher with 0.75% isopropyl myristate was the best formula that meets the specifications based on physical quality, effectiveness, and safety parameters.